Anti-Inflammatory Properties of Plant Derived Natural Products – A Systematic Review - Allijn, Iris E.; Brinkhuis, René P.; Storm, Gert; Schiffelers, Raymond M. (Current Medicinal Chemistry, 2019)
Traditionally, natural medicines have been administered as plant extracts, which are composed of a mixture of molecules. The individual molecular species in this mixture may or may not contribute to the overall medicinal effects and some may even oppose the beneficial activity of others. To better control therapeutic effects, studies that characterized specific molecules and describe their individual activity that have been performed over the past decades. These studies appear to underline that natural products are particularly effective as antioxidants and anti-inflammatory agents. In this systematic review we aimed to identify potent anti-inflammatory natural products and relate their efficacy to their chemical structure and physicochemical properties. To identify these compounds, we performed a comprehensive literature search to find those studies, in which a dose-response description and a positive control reference compound was used to benchmark the observed activity. Of the analyzed papers, 7% of initially selected studies met these requirements and were subjected to further analysis. This analysis revealed that most selected natural products indeed appeared to possess anti-inflammatory activities, in particular anti-oxidative properties. In addition, 14% of the natural products outperformed the remaining natural products in all tested assays and are attractive candidates as new anti-inflammatory agents.
Keywords: physicochemical properties